Revisiting the Alexander UFO Religious Crisis Survey (AUFORCS): Is There Really a Crisis? - Levin, Jeff (Journal of Scientific Exploration, 2012)
<span style="font-family: "Bookman Old Style","serif"; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This paper explores the tacit presumption that U.S. government disclosure of information regarding prior contact with extraterrestrials would precipitate a religious crisis (presuming that there is information to disclose). This issue has remained controversial since the earliest ufological writing, both government and academic, yet only minimal empirical evidence has been forthcoming. The present analysis is based on data collected as a part of the Alexander UFO Religious Crisis Survey (AUFORCS), a private study of Protestant, Roman Catholic, and Jewish clergy (N = 229) conducted in 1994 whose raw data only recently have been made public (to the author of this paper). The AUFORCS consisted of 11 statements about extraterrestrial contact, alien life, and a putative impact on religion, scaled on a five-point Likert metric requiring respondents to affirm their agreement or disagreement with each item. Findings from the AUFORCS data confirm that disclosure would not precipitate much of a religious crisis. Nor do there appear to be substantive differences in how leaders of respective religious traditions would react to such disclosure. The desirability of replicating this study through a large-scale national probability survey of the U.S. adult population is discussed. Keywords: ufology—extraterrestrials—religion—surveys